2019
DOI: 10.1111/sms.13448
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior in everyday life relates negatively to mood: An ambulatory assessment study

Abstract: Empirical evidence shows that physical behavior positively impacts human health. Recently, researchers have started to differentiate between physical activity and sedentary behavior showing independent effects on somatic health. However, whether this differentiation is also relevant for mood dimensions is largely unknown. For investigating the dynamic relationships between sedentary behavior and mood dimensions in daily life, ambulatory assessment (AA) has become the state‐of‐the‐art methodology. To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Further studies are needed to clarify the issue, whether mood is associated with sedentary behavior on a between‐subject level. In a previous work, 32 we reported that sedentary behavior negatively predicted two mood dimensions (ie, valence and energetic arousal) on a within‐subject level. Thus, the issue of a reciprocal relationship is a crucial question for future research endeavors, which may be of interest to address the question of causality.…”
Section: Discussionmentioning
confidence: 77%
“…Further studies are needed to clarify the issue, whether mood is associated with sedentary behavior on a between‐subject level. In a previous work, 32 we reported that sedentary behavior negatively predicted two mood dimensions (ie, valence and energetic arousal) on a within‐subject level. Thus, the issue of a reciprocal relationship is a crucial question for future research endeavors, which may be of interest to address the question of causality.…”
Section: Discussionmentioning
confidence: 77%
“…At each EMA prompt, participants were asked about their social (alone versus not alone) and environmental (home versus work versus leisure activities) contexts ( Table 1 ). Detailed information on the study was described elsewhere [ 4 ]. The study was approved by the institutional review board of the Karlsruhe Institute of Technology.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the wear-time criteria, we excluded 11 participants from the sample of study 1, 24 participants from the sample of study 2, and 13 participants from the sample of study 3. More details about the technical system used (the accelerometer and online platform) are described elsewhere [ 4 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Furthermore, using ecological momentary assessment analyses which allows for real-time assessment during everyday life, time spent in SB was negatively associated with valence and energised arousal. 24 However, whether SB accrued specifically during work hours contributes to these mood disturbances is unknown.…”
Section: Introductionmentioning
confidence: 99%